Analysis of Vitamin C Content in Loloh Cemcem (Spondias pinnata) and Stevia Leaves (Stevia rebaudiana B.) by UV-Vis Spectrophotometry Method - Elza Fitriani, Pande P.; Ariesta Wijaya Putra, Anak Agung Ngurah Dwi; Ary Widnyani, Ida Ayu Putu (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 8 No 2 (2021): Scientific Journal of Food Technology (September), 2021)
Vitamin C is one of the essential vitamins for humans that cannot be produced by the body itself. One of the fulfillments of vitamin C can be obtained through local nutraceutical, namely loloh cemcem. Loloh cemcem is one of healthy Balinese authentic beverage originating from Penglipuran Village, Bangli. Loloh cemcem is herb beverage made from forest ambarella leaves that are widely grown in Bangli. This study aimed to analyze the content of vitamin C in loloh cemcem with stevia leaves by UV-Vis Spectrophotometry Method. This study was a randomized complete design 1 factorial with 5 treatments of stevia leaves concentration and repeated 3 times. The results of the study on samples with stevia concentration of 5%, 7%, 9%, 11% and 13%, were 2.26%, 2.16%, 2.11%, 1.85% and 1.76% of vitamin C, respectively. This indicated that the more stevia concentrations given, the lower of vitamin C content could be produced. This product can be one of the options in the fulfillment of vitamin C for diabetics or those who limit their daily sugar intake to meet daily vitamin C needs.